Principles of Credit Analysis in BUMN/BUMD Banks in Indonesia - Indra Gunawan Purba; Warsiman Warsiman; Ervina Sari Sipahutar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The bank's business activities must be carried out in a more administrative nature and prioritize procedural aspects. BUMN / BUMD banks in providing credit to prospective debtors must follow the standards and standard mechanisms that apply within the bank itself or the Standard Operational Procedure (SOP), for that it is then required to comply with standards to arrive at a credit decision. The bank functions as a financial intermediary (intermediary financial) between parties with excess funds (surplus of funds) and parties requiring funds (deficit of funds). The main function of the bank is to mobilize public funds appropriately and quickly channel them to effective and efficient use or investment. A function like this is a "blood flow" for the economy and an increase in the standard of living. Without trust, this function will not work. Credit assessment is an activity carried out by credit analysts to assess whether credit to be given to debtors can be carried out. Assessment for consumptive credit is based only on the amount of salary earned in installments plus interest and the maximum will be determined at the amount of income.